2011
DOI: 10.1177/0363546511413378
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Correlation Between Serum Relaxin Concentration and Anterior Cruciate Ligament Tears Among Elite Collegiate Female Athletes

Abstract: Females with higher serum relaxin levels may be at increased risk for anterior cruciate ligament tears. Further investigation of the clinical utility of SRC testing is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 25 publications
3
123
1
4
Order By: Relevance
“…We were able to measure serum relaxin in generally low levels, and not all subjects had measurable relaxin levels. Dragoo et al noted detectable relaxin levels in 46 of 128 female athletes (36%) with an average relaxin level of 5.7 pg/mL in those without ACL tear and 12.1 pg/mL in those with tears [13]. Physiologic levels of circulating relaxin have been defined based on the pregnant female, but there is limited information on normal levels in postmenopausal women or older men, who made up the majority of our cohort.…”
Section: Discussionmentioning
confidence: 83%
“…We were able to measure serum relaxin in generally low levels, and not all subjects had measurable relaxin levels. Dragoo et al noted detectable relaxin levels in 46 of 128 female athletes (36%) with an average relaxin level of 5.7 pg/mL in those without ACL tear and 12.1 pg/mL in those with tears [13]. Physiologic levels of circulating relaxin have been defined based on the pregnant female, but there is limited information on normal levels in postmenopausal women or older men, who made up the majority of our cohort.…”
Section: Discussionmentioning
confidence: 83%
“…45,46 The percentages of those participants with no complete cycle appeared to be similar in athletes (14 of 74, 19%) and nonathletes (3 of 24, 12%), (P ¼ .47). Those percentages are much higher than the 4.75% of anovulatory athletic women recently reported by Dragoo et al 43 Of similar concern are the 29 participants (30%) with cycles shorter than 24 days or longer than 35 days. Cycles longer than 35 days are more likely to cause concern because high physical activity levels or poor nutritional states 5 (or both) can lengthen the cycle before the cycle is interrupted completely.…”
Section: Discussionmentioning
confidence: 55%
“…The concern that led to the development of these hypotheses was that the physical activity level of teenage female athletes was altering their hormonal balance in a way that made them more susceptible to anterior cruciate ligament (ACL) injury. In a recent, 5-year study of 143 female collegiate athletes, Dragoo et al 43 demonstrated a relationship between circulating relaxin, a collagenolytic hormone that participates in the remodeling process of the ACL, and the risk of ACL injury. When relaxin was detectable in the serum, 14 of 46 athletes (30%) tore their ACLs during their collegiate career; however, little is known about the cyclicity of relaxin, estrogen, and progesterone in normally menstruating women.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, combined administration of oestrogen and cyclic loading in pigs inhibited the mRNA expressions of collagen I, III and biglycan, whereas either oestrogen administration or cyclic loading alone increased the gene expression of only collagen I or collagen I and III, respectively [67]. Recent evidence showed that elite female athletes with ACL injury have higher serum relaxin concentration (SRC) than those without ACL tears; those with an SRC greater than 6.0 pg/mL showed over 4-fold increased risk of ACL tear [68]. Accordingly, results from these studies support a hypothesis that an increase in female hormones can be a risk factor of ACL injury.…”
Section: Hormonal Cycle and Ligamentous Laxitymentioning
confidence: 99%